Analisis Jumlah Fi’liyah Dalam Bahasa Arab - Muhammad Solihin Pranoto; Dea Ramadhani; Gita Adinda Sari; Kaifa Syita; Nadila Pratiwi Seragih; Siti Nadiah; Siti Nurpatdilla (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study analyzes the syntax of Arabic sentences, including the number of verbs. Verbs, which include verbs (predicates) and verbs (subjects), form the basis of Arabic sentence structure. This study aims to determine the position, i’rab, and relationships between words within a sentence. This study uses a descriptive qualitative research method with a library research approach, collecting data through Arabic journals, articles, and books. The results provide a deeper understanding of the relationships between syntactic constructions in Arabic.